Impact of Fundamental Factors on Stock Price in Nepalese Commercial Banks - Thapa, Samikshya (Nepalese Journal of Management, 2024)
This study examines the impact of fundamental factors on stock price in Nepalese commercial banks. Stock price is the dependent variable. The selected independent variables are earnings per share, dividend per share, price to earnings ratio, return on equity and size of the firm. The study is based on secondary data of 10 commercial banks with 100 observations for the study period from 2012/13 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of impact of fundamental factors on stock price in Nepalese commercial banks. The study showed that earnings per share has a positive impact on stock price. It means that increase in earnings per share leads to increase in stock price. In addition, dividend per share has a positive impact on stock price. It indicates that increase in dividend per share leads to increase in stock price. Similarly, price to earnings ratio has a positive impact on stock price. It indicates that increase in price to earnings ratio leads to increase in stock price. Further, the study also showed that return on equity has a positive impact on stock price. It means that higher the return on equity, higher would be the stock price. However, size of the firm has a negative impact on stock price. It shows that larger the size of the firm, lower would be the stock price.